Audiovisual Content for Children and Adolescents in Scandinavia - Jensen, Pia Majbritt; Novrup Redvall, Eva; Christensen, Christa Lykke; Lysne, Anders; Schanke Sundet, Vilde; Morsund, Ewa; Magnusson Qassim, Andreas; Mitric, Petar (Nordicom, University of Gothenburg, 2023)
Scandinavian children and adolescents’ media consumption has changed dramatically in the past decade. Films, series, and social media content on global platforms like Netflix, Disney+, and YouTube are now a major part of young people’s media diet, while encounters with domestic films, series, and platforms are in decline, severely challenging the ways domestic players think about young audiences. The contributions in this book explore these recent developments in the production, distribution, as well as reception of fictional content for children and adolescent audiences in the thoroughly digitalised and transnationalised Scandinavian countries.